Implementasi Media Pembelajaran Interaktif Berbasis Aplikasi CANVA pada Pembelajaran IPAS - Tri Ani Nur Aini (Journal of Primary Education Studies, 2025)
Canva application is a graphic design application that has many features such as making presentation slides, activity certificates, posters, brochures, video content and so on. The VA class teacher of MI Muhammadiyah Penaruaban utilizes this application to create interactive learning media by utilizing interactive power point features with the aim of adding to the learning experience of students so that they do not feel monotonous and bored. This study uses qualitative research with a field study approach to analyze the implementation of interactive learning media based on the Canva application in learning Natural and Social Sciences (IPAS) grade V in madrasah ibtidaiyah. Data were collected through observation, interviews, and documentation. Based on the research conducted, it shows that the implementation of Canva-based interactive learning media is well implemented through the stages of orientation, self-learning, individualized handling, enrichment, and transfer. Although the transfer stage is constrained by time constraints, the use of this media is overall effective in improving the quality of learning. This study recommends optimizing time management at each stage, especially material transfer, and considering the implementation of individual self-study to provide opportunities for each student to explore the material according to their own learning pace.